The lateral malleolar bony fleck classified by size and pathoanatomy: The IOFAS classification. Issue 4 (August 2018) - Wong-Chung, John; Tucker, Adam; Lynch-Wong, Matthew; Gibson, Desmond; O'Longain, Diarmaid S.
Highlights: Peroneal tendons dislocate without associated bony avulsion in Class I lesions. Tendons dislocate into subperiosteal sac in Class II lesions with small bony fleck. Tendons dislocate into fracture site in Class III lesions with big bony fleck. Dislocating peroneal tendons cause the bony avulsions in Classes II and III lesions. Calcaneal fractures cause Class IV lesions with no associated tendon dislocation. Abstract: Background: This study analyzes position of the peroneal tendons and status of the superior peroneal retinaculum (SPR) whenever a lateral malleolar bony flake fracture occurs. Methods: Twenty-four patients had a lateral malleolar bony fleck on anteroposterior ankle radiographs, either in isolation or associated with other hindfoot injuries. We studied size of the bony flecks, presence or absence of peroneal tendon dislocation and pathoanatomy on CT scans. Results: In 11 patients, a small bony fleck lies within the superior peroneal retinaculum and contiguous periosteum, which are stripped off the lateral fibula (Class II lesions). Tendons dislocate into the subperiosteal pouch thus formed, resembling Class I lesions without associated bony avulsion. Treatment for Class II is same as for Class I injuries. In 8 patients with a big bony fleck, tendons dislocate into the fracture site and SPR is intact (Class III lesions). In Class IV lesions, observed in 5 patients with 2-part calcaneal fracture/dislocation, SPR remains intact and peroneal tendons are not dislocated. The invariably large fleck results from the displacing lateral calcaneal fragment abutting against the fibula, whereas the dislocating tendons cause the bony avulsions in Classes II and III. Conclusions: Due to pathoanatomical differences, surgical approach and natural history of neglected lesions differ depending on size of the bony fleck. The SPR must not be incised in case of big Class III flecks.